Tipologi, Pola, dan Skenario Pengaturan Aktivitas Pengunjung di Candi Kidal - Himawan, Krishna Bhanu; Suryada, I Gusti Agung Bagus; Titisari, Ema Yunita; Paramadhyaksa, I Nyoman Widya (Jurnal Arsitektur Universitas Udayana; Vol 13 No 01 (2025): Jurnal Arsitektur, Universitas Udayana, 2025)
Candi Kidal, the oldest historical site from the Singasari Kingdom era located in Malang, East Java, not only holds historical value in its construction, but also encompasses a broad philosophy within the ornaments of each part of the temple. This attracts various types of visitors, such as researchers, archaeologists, students, and tourists, making the temple a place for learning, recreation, and religious activities. However, the existing circulation pattern poses a challenge to the aesthetic effectiveness of the temple site, and the management of tourist activities that could threaten the physical integrity of the temple, leading to the deterioration of its historical value and a decrease in the quality of the experience for each type of visitor. Therefore, there is a need to propose effective circulation pattern and zoning to preserve the physical and aesthetic integrity of the Candi Kidal site and enhance new and engaging experiences for various types of visitors. The method used involves qualitative methods through field observations and interviews. This paper describes the concept of circulation and zoning arrangement at the Candi Kidal site, emphasizing the effectiveness of pedestrian pathways for different types of visitors. The final results of the study present a design concept for the circulation arrangement at the Candi Kidal site as a proposed solution to enhance its potential and address the challenges it faces. Keywords: Candi Kidal, visitor typology, circulation, arrangement